Strategic Drift in International Non-Governmental Development Organizations - Putting Strategy in the Background of Organizational Change - Dopson, S; Harris, M; Fitzpatrick, R (John Wiley & Sons Ltd., 2009)
Although the use of strategic planning has become widespread in INGDOs they have often been accused of strategic drift — continuous change in their strategic directions with plans only loosely coupled to their activities. However, the way that they prioritize their activities, and the reasons why strategic drift occurs has generally escaped in-depth research. This article draws on detailed, qualitative research of strategic planning meetings at the executive levels in a major INGDO, carried out between July 2006 and December 2007 to identify the reasons why strategic drift occurs and the role of strategic planning. It was found that by deliberately crafting multiple, ambiguous, and ambitious strategies, managers were able to effect organizational change, not by literal strategy implementation, but by using these strategies as metaphors to harness consensus and legitimacy in key stakeholder groups. Senior managers utilize the symbols, language and deliberative arenas of formal strategic planning to effect organizational change; however, strategy, in rational terms, needs to be located in the background for its role to be properly understood. The research unpacks complex decision-making processes in an INGDO and, contrary to normative literature, recommends that, in order to avoid inflationary planning, managers should not take their strategy literally.